2020
DOI: 10.3390/ma13061481
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of ABS Barium Ferrite Composites

Abstract: In this work, a process for the realization of new polymer matrix composites with nanosized barium ferrite (BaFe12O19) as ferrimagnetic filler, acryl butadiene styrene (ABS) as polymer matrix and an extrusion-based method, namely fused filament fabrication (FFF), as 3D printing method will be described comprehensively. The whole process consists of the individual steps material compounding, rheological testing, filament extrusion, 3D-printing via FFF and finally a widespread specimen characterization regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 29 publications
(43 reference statements)
1
33
0
Order By: Relevance
“…This can be observed in SEM analysis. Similar results were also found in the research of Hanemann et al (2020) who found that BaFe 12 O 19 particles acting as discontinuities in the ABS matrix generated defects, such as voids within one layer as well as between layers and delamination of printed layers in the specimen during the printing process 13 . The tensile strength of PLA‐Si‐10, PLA‐Si‐20, PLA‐Si‐30, and PLA‐Si‐40 was 20.82, 24.82, 21.83, and 15.71 MPa, respectively.…”
Section: Resultssupporting
confidence: 88%
“…This can be observed in SEM analysis. Similar results were also found in the research of Hanemann et al (2020) who found that BaFe 12 O 19 particles acting as discontinuities in the ABS matrix generated defects, such as voids within one layer as well as between layers and delamination of printed layers in the specimen during the printing process 13 . The tensile strength of PLA‐Si‐10, PLA‐Si‐20, PLA‐Si‐30, and PLA‐Si‐40 was 20.82, 24.82, 21.83, and 15.71 MPa, respectively.…”
Section: Resultssupporting
confidence: 88%
“…In general, an increase in the curing time should enhance the mechanical properties, for instance, due to a better intermixture accompanied with an enhanced polymer chain entanglement. Unfortunately, a clear correlation between curing time and mechanical properties cannot be found here, which may be attributed to the layer-by-layer fabrication process generating defects, as is prominently known for FFF printing [31]. A closer look at the fracture images after tensile testing verifies this possible explanation for the observed data scattering (Figure 13).…”
Section: Single-materials Printmentioning
confidence: 71%
“…The use of functional composites, e.g., with dielectric or magnetic properties for the realization of ceramic or metallic parts, requires additional melt-compounding steps such as mixing-kneading and filament extrusion [8,9,11,31]. Due to the round filament shape and its deposition in a layer-by-layer manner, poor inter-layer adhesion within one component is one of the major drawbacks of single-material [31] and two-component FFF printing [32]. Commercial multi-component 3D InkJet printers are available at prices upwards of €30,000, enabling geometric resolutions better than 50 µm in x-, y-and z-directions.…”
Section: Introductionmentioning
confidence: 99%
“…A screw feeder (Schenck process Mechatron Coin-Flex Screw Feeder) allowed precise control of the material supply to the throat of the twin screw extruder. This setup was selected due to the enhanced mixing capabilities of the twin screw system over a traditional single screw setup, rooted in higher overall shear forces that allow deagglomerating the particles of the filler [17].…”
Section: Twin Screw Extrusionmentioning
confidence: 99%